Role of the China South–South cooperation hegemonic strategy as an “early emulation” in a context of systemic chaos - Cabrera García, Ada Celsa; Lo Brutto, Giuseppe (Frontiers in Political Science, 2023)
This study seeks to contribute to the thesis that China is directing its efforts toward the construction of a set of institutions that are presented as an alternative interstate subsystem to the one that emerged in the second postwar period. In this research, we made progress in locating the main elements from which we prefigure one of the features of that project. This is the strategy that, based on the cooperation scheme implemented by China through the Belt and Road Initiative (BRI), the Global Development Initiative (GDI)1 and the Global Security Initiative (GSI),2 manifests itself in a kind of “early emulation” of the North American hegemonic strategy of the second postwar period. “Emulation” of the United States (US) is synthesized in a double process: first, in the way in which China is currently articulating an institutional framework under the intensification of the present systemic chaos, that is, in a previous or “early” moment with respect to that in which we could consider the clear rise of a new hegemonic power. This framework operates under the logic of a political dialog that allows trade agreements and promotes a development strategy based on structural change. Second, in a similar way to the multilateral consensus that underpinned the US project based on the promotion of “development” from the north to the south and with a fundamental role for cooperation and aid, China today deploys a similar argument promoting the scope of “a community of shared future”3 with its strategic partners and to which more and more states look to join, where the GDI and the GSI are fundamental axes.